Robot sensors process based on generalized Fermatean normal different aggregation operators framework - Palanikumar, Murugan; Kausar, Nasreen; Garg, Harish; Ahmed, Shams Forruque; Samaniego, Cuauhtemoc (AMER INST MATHEMATICAL SCIENCES-AIMS, 2023)
Novel methods for multiple attribute decision-making problems are presented in this paper using Type-II Fermatean normal numbers. Type-II Fermatean fuzzy sets are developed by further generalizing Fermatean fuzzy sets and neutrosophic sets. The Type-II Fermatean fuzzy sets with basic aggregation operators are constructed. The concept of a Type-II Fermatean normal number is compatible with both commutative and associative rules. This article presents a new proposal for Type -II Fermatean normal weighted averaging, Type-II Fermatean normal weighted geometric averaging, Type-II generalized Fermatean normal weighted averaging, and Type-II generalized Fermatean normal weighted geometric averaging. Furthermore, these operators can be used to develop an algorithm that solves MADM problems. Applications for the Euclidean distance and Hamming distances are discussed. Finally, the sets that arise as a result of their connection to algebraic operations are emphasized in our discourse. Examples of real-world applications of enhanced Hamming distances are presented. A sensor robot's most important components are computer science and machine tool technology. Four factors can be used to evaluate the quality of a robotics system: resolution, sensitivity, error and environment. The best alternative can be determined by comparing expert opinions with the criteria. As a result, the proposed models' outcomes are more precise and closer to integer number delta. To demonstrate the applicability and validity of the models under consideration, several existing models are compared with the ones that have been proposed.
Keywords: MADM; aggregating operator; Type-II FNWA; Type-II FNWG; Type-II GFNWA; Type-II GFNWG; CRITERIA DECISION-MAKING; FUZZY; EXTENSION; TOPSIS; Mathematics